Choosing a mouse model of venous thrombosis: a consensus assessment of utility and application. (30th March 2019) - Diaz, Jose A.; Saha, Prakash; Cooley, Brian; Palmer, Olivia R.; Grover, Steven P.; Mackman, Nigel; Wakefield, Thomas W.; Henke, Peter K.; Smith, Alberto; Lal, Brajesh K.
Abstract : Summary: Murine models are widely used valuable tools to study deep vein thrombosis (VT). Leading experts in VT research came together through the American Venous Forum to develop a consensus on maximizing the utility and application of available mouse models of VT. In this work, we provide an algorithm for model selection, with discussion of the advantages, disadvantages, and applications of the main mouse models of VT. Additionally, we provide a detailed surgical description of the models with guidelines to validate surgical technique.